Multiple resources and their sustainable development in Urban Underground Space. (May 2016) - Li, XiaoZhao; Li, Congcong; Parriaux, Aurèle; Wu, Wenbo; Li, HuanQing; Sun, Liping; Liu, Chao
Highlights: The resource-based "bottom-up" concept in UUS planning is introduced. Study on evaluation methodology and investigations in typical cases are presented. Resource attributes of UUS and evaluation index system are investigated. Conflicts between urban underground multiple resource developments are identified. The sustainable principles and methods are discussed. Abstract: Traffic congestion and ground space scarcity are increasing the need to find more space in the urban underground. The demand-driven "top-down" planning of Urban Underground Space (UUS) is common worldwide. As natural resource, the endowments of UUS are different in different regions. Consideration of UUS resource endowments, which can be called "bottom-up" thinking, should be integrated into planning. The evaluation method of UUS resource and investigation results in typical cases are being presented in the paper. It is important for urban development to utilize the underground space. Meanwhile, we should also be aware that there are multiple valuable resources in urban underground. Besides space, there are also water, energy and geo-materials. The paper will discuss how to consider these different resources in urban development. There might be conflicts between the developments of different urban underground resources. The paper investigated the interactions between these developments, revealed some serious impacts and typical conflict modes. The identification of conflicts is a basis for the coordination and synergy of these developments. For sustainable development of city, it is needed to understand and scientifically evaluate the multiple urban underground resources, then holistically plan and manage the developments. Structure and properties of urban underground geological body determine the engineering conditions of UUS and resource attributes of urban underground. Since 2003, China has been conducting pilot projects of Urban Geological Investigation (UGI) programs in some large cities. The paper will also show how to consider the influence of geological conditions in urban underground resource evaluation and UUS planning.